Leucocyte profiles of Arctic marine birds: correlates of migration and breeding phenology. (26th June 2015) - Mallory, Mark L.; Little, Catherine M.; Boyd, Ellen S.; Ballard, Jennifer; Elliott, Kyle H.; Gilchrist, H. Grant; Hipfner, J. Mark; Petersen, Aevar; Shutler, Dave
Abstract : We examined white blood cell profiles of marine birds breeding in the Arctic, as an index of stress. Within species, birds that had to migrate farther had higher heterophil:lymphocyte ratios during incubation (i.e., residual stress) than those that migrated short distances. These reference values will be important as global warming and anthropogenic activities change the Arctic marine landscape. Abstract : Most Arctic marine birds are migratory, wintering south of the limit of annual pack ice and returning north each year for the physiologically stressful breeding season. The Arctic environment is changing rapidly due to global warming and anthropogenic activities, which may influence the timing of breeding in relation to arrival times following migration, as well as providing additional stressors (e.g. disturbance from ships) to which birds may respond. During stressful parts of their annual cycle, such as breeding, birds may reallocate resources so that they have increased heterophil-to-lymphocyte ratios in their white blood cell (leucocyte) profiles. We analysed leucocyte profiles of nine species of marine birds to establish reference ranges for these species in advance of future Arctic change. Leucocyte profiles tended to cluster among taxonomic groups across studies, suggesting that reference values for a particular group can be established, and within species there was evidence that birds from colonies that had to migrate farther had higher heterophil-to-lymphocyte ratios during incubation than those that did not have to travel as far, particularly for species with high wing loading.